2022
DOI: 10.3390/rs14164093
|View full text |Cite
|
Sign up to set email alerts
|

Elevation Extraction from Spaceborne SAR Tomography Using Multi-Baseline COSMO-SkyMed SAR Data

Abstract: SAR tomography (TomoSAR) extends SAR interferometry (InSAR) to image a complex 3D scene with multiple scatterers within the same SAR cell. The phase calibration method and the super-resolution reconstruction method play a crucial role in 3D TomoSAR imaging from multi-baseline SAR stacks, and they both influence the accuracy of the 3D SAR tomographic imaging results. This paper presents a systematic processing method for 3D SAR tomography imaging. Moreover, with the newly released TanDEM-X 12 m DEM, this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Recent studies by Chen [7] ,Liu [8] ,Wang [9] ,He [10] , and Feng [11] have demonstrated the efficacy of PS-InSAR in diverse applications, ranging from mining subsidence detection to landslide monitoring and seismic event analysis. These studies showcase the versatility of PS-InSAR in capturing spatial and temporal variations in surface deformation, providing a foundation for our exploration in the unique setting of the Bortala Mongol Autonomous Prefecture.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies by Chen [7] ,Liu [8] ,Wang [9] ,He [10] , and Feng [11] have demonstrated the efficacy of PS-InSAR in diverse applications, ranging from mining subsidence detection to landslide monitoring and seismic event analysis. These studies showcase the versatility of PS-InSAR in capturing spatial and temporal variations in surface deformation, providing a foundation for our exploration in the unique setting of the Bortala Mongol Autonomous Prefecture.…”
Section: Introductionmentioning
confidence: 99%
“…Chang et al, enhanced SAR 3D imaging by combining DBF and BSS, improving echo separation in uneven terrain and simplifying data processing for urban building structures in 2022 [21]. Based on 14 satellite SAR images, the author of [22] using Compressed Sensing (CS) to realize super-resolution 3D TomoSAR imaging in 2022, which was suitable for elevation extraction of urban buildings. The authors of [23] proposed a distributed SAR high-resolution wideband (HRWS) 3D imaging method in 2023, which overcame the limitation of traditional single-satellite antennas by using 14channel number SAR data.…”
Section: Introductionmentioning
confidence: 99%